Play Fairway analysis of geothermal resources across the State of Hawai'i: 4. Updates with new groundwater chemistry, subsurface stress analysis, and focused geophysical surveys. (July 2020) - Lautze, Nicole; Ito, Garrett; Thomas, Donald; Frazer, Neil; Martel, Stephen J.; Hinz, Nicholas; Tachera, Diamond; Hill, Graham; Pierce, Herbert A.; Wannamaker, Philip E.; Martin, Thomas
Highlights: Fourth paper in series on a geothermal resource assessment across the State of Hawaii. Provides results of groundwater sampling in 10, and geophysics in 3, areas of state. Developed new method for computing topographic stress. Present updated statewide resource probability and confidence maps. Updated roadmap for next phase of exploration activities. Abstract: This paper is the fourth in a series on a play fairway analysis of geothermal resources across the State of Hawai'i. Here we describe recent exploration activities that include groundwater sampling in ten locations statewide, as well as geophysical surveys on Lāna'i, across the SW rift of Haleakalā Volcano (Maui), and surrounding Mauna Kea Volcano (Hawai'i Island). We derive a first-order method for computing topographic stress using Green's functions, finding that topography can induce appreciable crustal stress. We develop a new method for incorporating depth information about resistivity, density, and topographic stresses into our previously published equations to calculate resource probability and confidence. We incorporate newly collected and modeled data into our calculations to update statewide maps of probability and confidence. Lāna'i Island and southeast Mauna Kea are identified as the top targets for exploratory drilling. The east rift of Haleakalā Volcano, the southern-most region of Mauna Loa's SW rift (Hawai'i Island), and central Kauai are identified as targets for geophysical surveying.